Perancangan dan Pemanfaatan Penampung Air Hujan dengan Filtrasi Sederhana Skala Unit Perumahan Villa Citra Bantarjati: Design of Rainwater Storage with Simple Filtration in House Unit Scale in Villa Citra Bantarjati Housing - Zuliarti, Armin; Saptomo, Satyanto Krido (Jurnal Teknik Sipil dan Lingkungan, 2021)
Bogor city is included in the region with high rainfall with an average annual rainfall of 3.500 – 4.000 mm so that the potential for rainwater harvest. This research was conducted to plan the volume of rainwater reservoirs that can be applied at the scale of Villa Citra Bantarjati housing units and design simple filtration tools to improve the physical quality of rainwater that can be used to support domestic needs. This study was conducted using primary data covering the area of roofs used in rainwater harvesting as well as secondary data in the form of maximum rainfall data in the last 15 years. Water quality testing is conducted by physical quality test of rainwater before and after passing the design of a simple filter tool to produce water quality that meets class II water quality standards. The area of the roof used to catch rainwater is 25 m2, so the average volume of availability accommodated in rainwater reservoirs is 155,31 lt/day with a water loss factor due to runoff of 20%. The capacity of rainwater reservoirs that meet domestic water needs is 330 lt. The design of this simple filter is able to improve the physical quality of rainwater with a predetermined arrangement of filter media.